Peran Guru Bk/Konselor dan Guru Mata Pelajaran dalam Meningkatkan Motivasi Belajar Siswa yang Memperoleh Hasil Belajar Rendah - Sari, Mega Mulya; Taufik, Taufik; Yusri, Yusri (Universitas Negeri Padang, 2014)
The Implementation of a good role and planned by the counseling/counselorâ€™s teacher in schools (counseling teacher) and teachers generally can increase learning motivation of students who have a low learning result. This is based on the real phenomenon that shows students with low learning result tend to have a low learning motivation. This study aims to describe the role that is made by a teacher/counselor in improving learning motivation of students with low learning result. In its implementation, the role of the counselor teacher was affected through the services, including through information services and individual counseling services, and the role of the teacher were carried out through the guidance activities in the classroom and outside of the classroom. The type of this research is quantitative descriptive, the population in this study ,all teachers and counselorÂ in SMAN 30 Padang, counselorÂ teacher sample are 30 and teachers of subjects are 80, this study uses the instrument in the form of the now. The research of this study reveal: the role of subjects teacher and counselor teacher in improving the learning motivation of students with low learning result.